From entity to process: toward more process-based theorizing in the field of organizational change. Issue 1 (5th March 2018) - Wenzel, Matthias; Koch, Jochen
Abstract : Purpose: The purpose of this paper is to make a case for more process-based theorizing in the field of organizational change. Design/methodology/approach: To emphasize the importance of a process perspective on organizational change, this paper challenges the prevalent theorizing approach that treats organizational change as entity and argues that process-based theorizing can help researchers gain a better understanding of organizational change. Findings: To direct future research toward more process-based theorizing, this paper proposes a systematic four-step procedure for the analysis of qualitative data that helps researchers theorize organizational change from a process perspective. Originality/value: Overall, this paper contributes to theorizing efforts in the field of organizational change by offering a reflective account on the challenges that entity-based theorizing entails, strengthening the position of process-based theorizing in light of these challenges and providing an outlook on how scholars can develop theoretical insights on organizational change from a process perspective.